Thermoelastic damping in micro and nano-mechanical resonators utilizing entropy generation approach and heat conduction model with a single delay term - Kumar H.; Mukhopadhyay S. (My University, 2025)
Analysis of thermoelastic damping (TED) of micro and nano-beam resonators plays a very important role in designing the resonator with high-quality factors. TED of micro and nano-beam resonators has therefore been an interesting and challenging area of research in recent years. Prediction of TED is more challenging under the effect of non-Fourier heat conduction. In the past, several works have been dedicated to TED modeling with the influence of non-Fourier heat conduction in view of the fact that non-Fourier heat conduction model is more relevant for analysis of TED for small scale devices. The present work aims to investigate TED in micro and nano-mechanical resonators utilizing non-Fourier heat conduction model with a single delay term introduced by Quintanilla in 2011. We derive an explicit formula of the quality factor for TED based on the entropy generation approach. With the help of numerical results, we present the influence of TED in the context of normalized frequency as well as beam thickness. Further, the effects of the time delay parameter and the material constants on TED have been discussed in detail. The results of the present model are compared to those obtained for GN-III model. It has been observed that the current model offers a high-quality factor as compared to GN-III model. © 2019 Elsevier Ltd